2013
DOI: 10.1007/s13277-013-1097-0
|View full text |Cite
|
Sign up to set email alerts
|

ARID5B gene rs10821936 polymorphism is associated with childhood acute lymphoblastic leukemia: a meta-analysis based on 39,116 subjects

Abstract: Childhood acute lymphoblastic leukemia (ALL) is the leading cause of cancer-related deaths among children. Two recent genome-wide association studies and several replicated studies have provided convincing evidence that inherited genetic variation in ARID5B contributes to childhood ALL predisposition. In the present study, we performed a meta-analysis to systematically summarize the association between ARID5B genetic polymorphism and the risk for ALL. We conducted a search of case-control studies on the associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 24 publications
0
15
0
1
Order By: Relevance
“…After the extensive replication studies, some loci can be validated in all independent cohorts (eg, ARID5B ), whereas inconsistent associations were noticed in other loci (eg, PIP4K2A ), mostly due to small sample size and diverse patient characteristics. Systematic review and meta-analyses have been conducted for signals at ARID5B , IKZF1 , and CEBPE loci, 16 18 but not for PIP4K2A-BMI1 locus, which was firstly identified in our multiethnic GWAS. 5 Under this case, meta-analyses acted as a powerful tool to figure out the affecting factors, and potentially provided a clue on searching causal variants.…”
Section: Discussionmentioning
confidence: 99%
“…After the extensive replication studies, some loci can be validated in all independent cohorts (eg, ARID5B ), whereas inconsistent associations were noticed in other loci (eg, PIP4K2A ), mostly due to small sample size and diverse patient characteristics. Systematic review and meta-analyses have been conducted for signals at ARID5B , IKZF1 , and CEBPE loci, 16 18 but not for PIP4K2A-BMI1 locus, which was firstly identified in our multiethnic GWAS. 5 Under this case, meta-analyses acted as a powerful tool to figure out the affecting factors, and potentially provided a clue on searching causal variants.…”
Section: Discussionmentioning
confidence: 99%
“…In all cases of childhood leukemia, ~80% are ALL, which represents ~25% of cancers in children diagnosed <15 years of age in the United States in 2014 (2). Although the etiology of ALL is largely unknown, it has been proposed that multiple gene alterations, including inactivation of tumor suppressor genes, activation of proto-oncogenes and chromosomal rearrangements, in addition to gene-environmental interplay, are involved in disease development (1,3,4). Chromosomal abnormalities, including homozygous deletions and loss of heterozygosity, are among the most common characteristics of human tumors.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis study of 13 case-control studies involving 7147 patients and 31,969 controls reported that ARID5B rs10821936 SNP is associated with a high risk for ALL. 36 Functional studies are needed to explore how this SNP contributes to the increased risk of ALL. Due to conflicting studies relating to possible genderspecific associations with ALL, a stratified analysis of ALL between males and females was also performed.…”
Section: Discussionmentioning
confidence: 99%